Elements of French deaf heritage - Hedberg, Ulf; Lane, Harlan, 1936-2019 (Gallaudet University Press, 2020)
"Elements of French Deaf Heritage is an examination of how Deaf ethnicity evolved in France via key elements such as Deaf schools, associations of the Deaf, congresses of the Deaf, presses, and key "founders" such as Deaf artists. Intended as a reference book, the aim of the authors is to disseminate the extensive amount of information they've collected so the reader can begin to understand the underlying forces how of Deaf culture was formed both in France and more generally"--